Bioactive metabolites of Streptomyces misakiensis display broad-spectrum antimicrobial activity against multidrug-resistant bacteria and fungi - Abdelaziz, Rewan; Tartor, Yasmine H.; Barakat, Ahmed B.; EL-Didamony, Gamal; Gado, Marwa M.; Berbecea, Adina; Radulov, Habil dr. Isidora (Frontiers in Cellular and Infection Microbiology, 2023)
Background Antimicrobial resistance is a serious threat to public health globally. It is a slower-moving pandemic than COVID-19, so we are fast running out of treatment options. Purpose Thus, this study was designed to search for an alternative biomaterial with broad-spectrum activity for the treatment of multidrug-resistant (MDR) bacterial and fungal pathogen-related infections. Methods We isolated Streptomyces species from soil samples and identified the most active strains with antimicrobial activity. The culture filtrates of active species were purified, and the bioactive metabolite extracts were identified by thin-layer chromatography (TLC), preparative high-performance liquid chromatography (HPLC), nuclear magnetic resonance (NMR) spectroscopy, and gas chromatography-mass spectrometry (GC-MS). The minimum inhibitory concentrations (MICs) of the bioactive metabolites against MDR bacteria and fungi were determined using the broth microdilution method. Results Preliminary screening revealed that Streptomyces misakiensis and S. coeruleorubidus exhibited antimicrobial potential. The MIC50 and MIC90 of S. misakiensis antibacterial bioactive metabolite (ursolic acid methyl ester) and antifungal metabolite (tetradecamethylcycloheptasiloxane) against all tested bacteria and fungi were 0.5 μg/ml and 1 μg/mL, respectively, versus S. coeruleorubidus metabolites: thiocarbamic acid, N,N-dimethyl, S-1,3-diphenyl-2-butenyl ester against bacteria (MIC50: 2 μg/ml and MIC90: 4 μg/mL) and fungi (MIC50: 4 μg/ml and MIC90: 8 μg/mL). Ursolic acid methyl ester was active against ciprofloxacin-resistant strains of Streptococcus pyogenes, S. agalactiae, Escherichia coli, Klebsiella pneumoniae, and Salmonella enterica serovars, colistin-resistant Aeromonas hydrophila and K. pneumoniae, and vancomycin-resistant Staphylococcus aureus. Tetradecamethylcycloheptasiloxane was active against azole- and amphotericin B-resistant Candida albicans, Cryptococcus neoformans, C. gattii, Aspergillus flavus, A. niger, and A. fumigatus. Ursolic acid methyl ester was applied in vivo for treating S. aureus septicemia and K. pneumoniae pneumonia models in mice. In the septicemia model, the ursolic acid methyl ester-treated group had a significant 4.00 and 3.98 log CFU/g decrease (P < 0.05) in liver and spleen tissue compared to the infected, untreated control group. Lung tissue in the pneumonia model showed a 2.20 log CFU/g significant decrease in the ursolic acid methyl ester-treated group in comparison to the control group. The haematological and biochemical markers in the ursolic acid methyl ester-treated group did not change in a statistically significant way. Moreover, no abnormalities were found in the histopathology of the liver, kidneys, lungs, and spleen of ursolic acid methyl ester-treated mice in comparison with the control group. Conclusion S. misakiensis metabolite extracts are broad-spectrum antimicrobial biomaterials that can be further investigated for the potential against MDR pathogen infections. Hence, it opens up new horizons for exploring alternative drugs for current and reemerging diseases.